“Cultural Translation” vs. “Poetic Translation”? A Problematic Categorization in Translating Poetry. The Case of Arthur Rimbaud’s "Ophélie" in German - Forassaco, Dennis (Estudios de Traducción, 2013)
Translating poetry represents the most arduous duty for the literary translator. Despite of its artistic nature translating verses can be object of the scientific investigation and contribute to the development of the translation studies. The following paper aims to examine the dynamics and the tensions being generated between source-text and the cultural norms of the target-text, which act on the translator and considerably influence the filter. The comparison of translations becomes a fruitful method of inquiry, as it permits to shine a light on the development of translating theory in a diachronic perspective, which contributes to the study of the comparative cultural history, as well. This is the goal of the following comparison between two German translations of Rimbaud’s Ophélie.